(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the context of the development of such world processes as globalization and regionalism, the researchers note, the importance of the religious factor in the life of modern society is sharply increasing. It is known that a sharp increase in the religious factor in life always occurs at sharp turns in history. And the current stage in the development of mankind, when it has reached a new level of its development, is also marked by the strengthening of the role of religion in the life of society. That is why the issues of interaction between different religions, believers, issues of tolerance, including religious tolerance, are so urgent today.